2021
DOI: 10.1186/s13068-021-01980-4
|View full text |Cite
|
Sign up to set email alerts
|

Water reuse and growth inhibition mechanisms for cultivation of microalga Euglena gracilis

Abstract: Background Microalgae can contribute to more than 40% of global primary biomass production and are suitable candidates for various biotechnology applications such as food, feed products, drugs, fuels, and wastewater treatment. However, the primary limitation for large-scale algae production is the fact that algae requires large amounts of fresh water for cultivation. To address this issue, scientists around the world are working on ways to reuse the water to grow microalgae so that it can be gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…So far, the research regarding the recycling or removal of mediators in BESs is rather scarce but can benefit readily from the research efforts in other relevant fields. For instance, the reuse of culture medium has been a long‐term desire in biotechnology (especially for large scale cultivation) to reduce the operation cost [21–23] . Membrane or chromatography‐based approaches are used mostly to separate and recycle usable nutrients.…”
Section: Downstream Removal and Recycling Of Redox Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the research regarding the recycling or removal of mediators in BESs is rather scarce but can benefit readily from the research efforts in other relevant fields. For instance, the reuse of culture medium has been a long‐term desire in biotechnology (especially for large scale cultivation) to reduce the operation cost [21–23] . Membrane or chromatography‐based approaches are used mostly to separate and recycle usable nutrients.…”
Section: Downstream Removal and Recycling Of Redox Mediatorsmentioning
confidence: 99%
“…For instance, the reuse of culture medium has been a long-term desire in biotechnology (especially for large scale cultivation) to reduce the operation cost. [21][22][23] Membrane or chromatography-based approaches are used mostly to separate and recycle usable nutrients. These might also be applicable in BESs for mediator recycling, while the economic feasibility might be a key limitation.…”
Section: Downstream Removal and Recycling Of Redox Mediatorsmentioning
confidence: 99%
“…Another commonly used purification method is the removal of organics by adsorption, which is widely applied in the removal of pollutants from water, especially employing activated carbon absorption (ACA), because it is costeffective and easily adaptable. In a recent study, 40 ACA treatment has been shown to remove or convert humic acid into nutrients and water recovery. In our study, SCWG and ACA treatments were applied as purification steps of the aqueous product from microalgae HTL.…”
Section: Dry Content Mass Massmentioning
confidence: 99%
“…Microalgae release into their cultivation media various organic compounds with various molecular masses, including aromatic amino acids such as tryptophan and tyrosine, heterocyclic pigments such as biopterin, proteins, etc., that generate humic-like substances, algal organic matter (AOM) [ 182 ]. This dissolved organic matter that results from microalgae organisms is also called humic matter due to its aromaticity (π-π systems) related to significant fluorescence [ 183 , 184 ]. In several cases, accumulations of this organic matter during microalgae cultivation block water reuse.…”
Section: Humic Substances As Microalgae Biostimulantsmentioning
confidence: 99%